The Effect of Knee Lift Jump Exercises on Increasing Leg Muscle Explosive Power in Beginners - Pratama, Budi; Syamsuramel, Syamsuramel; Yusfi, Herri; Destriani, Destriani (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This research aims to assess the impact of knee lift jump training on increasing leg muscle explosive power in novice gymnasts at the Pengda Persani Palembang club. The study involved 30 gymnasts from the research population, with the same sample size. In this study, an experimental research method was employed involving data collection through sports tests and measurements. The research utilized a pre-test and post-test one-group design, with the pre-test conducted before applying the treatment and the post-test conducted afterward. The study aimed to evaluate the impact of knee lift jump exercises on improving lower limb muscle explosive power among members of the Pengda Persani Palembang gymnastics club. Based on research data obtained from vertical jump tests conducted on 30 novice gymnasts in the Pengda Persani Palembang club, the following key findings were observed: - Pre-test Mean: 51.63, Standard Deviation: 16.059, Range: 50, Normality test result: 0.087 - Post-test Mean: 59.13, Standard Deviation: 15.690, Range: 54, Normality test result: 0.109 The t-test resulted in a p-value of 0.000.